Respuesta :

lime52
First, let's find y by substituting x for what x is equal to, so that we will only have one variable and we can solve the equation.

x = y    Given
x - 3y = 4    Given
y - 3y = 4   Substitute x for y, because x = y
-2y = 4    Subtract
y = -2   Divide

Now, to find x, we need to substitute our value for y back into the original equation.

x = y
x = -2   Substitute -2 for y, since y = -2

The correct answer is (-2,-2).

Hope this helps!


if x = y then put x where y is or y wherever x is.
x-3x=4
-2x = 4
x = -2

now plug that in to find y
x-3y = 4
-3y = 4+2
-3y = 6
y = -2